Hubungan Konsumsi Purin dan Hipertensi terhadap Serangan Berulang Atritis Gout pada Pasien di Puskesmas Kecamatan Krembangan pada Tahun 2022 - Crisantika, Eucharistia; Sintia, Nely; Wahyuni, Chatarina Umbul (Universitas Airlangga, 2024)
Background: Gout arthritis is a systemic disease resulting from the deposition of monosodium urate (MSU) crystals. The prevalence of gouty arthritis in Indonesia is increasing. The general prevalence of gouty arthritis is 1-4% of the general population. In 2013 in East Java, the incidence of gouty arthritis reached 26.4%. Meanwhile in Surabaya, in 2011 the prevalence of gout arthritis touched 56.8%. Untreated gouty arthritis can result in repeated attacks on the sufferer. This can cause disruption of quality of life, disability, and even loss of work productivity. Objectives: The purpose of this study was to analyze the relationship between purine consumption and history of hypertension with repeated attacks of gouty arthritis in patients at the Puskesmas Kecamatan Krembangan. Methods: This research was an observational study used a case-control study design, namely comparing cases from the case group and the controlled group with a ratio of 1:2. The population in this research was all sufferers of gouty arthritis who lived in the working area of the Krembangan District Public Health Center, Surabaya City, totaling 53 people. Sampling was done by purposive sampling technique. Test data analysis used the spearman test to determine the relationship between the two variables. Results: The results of this study was shown by the p-valued in the variable purine consumption pattern which included a value of 0.026 with a r-value = 0.387 which meant there was a relationship between purine consumption patterns with repeated attacked with weak relationship strength. The p-value in the hypertension variable is 0.741 and the r-value = 0.06 which meant that there is almost no relationship between a history of hypertension and repeated attacked of gouty arthritis. Conclusions: The consumption pattern of purines has a relationship with recurrent attacks of gouty arthritis with a weak relationship strength, while a history of hypertension has no relationship with the occurrence of recurrent attacks of gouty arthritis.